Unfinished Stories, Incomplete Revolutions: Gender and Women’s History in the Journal of the Canadian Historical Association, 1922–2022 - Campbell, Lara (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2023)
Over a century, the JCHA has published increasing numbers of innovative articles in gender and women’s history. Historians have addressed foundational debates about the connection between public and private spheres, transnational and postcolonial turns, the discursive construction of gender, and the history of masculinity. The expansion of women’s and gender history in the decade of the 1990s consolidated the field, but also created a sense of disquiet as historians challenged national narratives and disciplinary authority in the historical profession. Despite decades of rich historiographical insights, however, powerful and systemic silences remain in the Journal, including the intersection of gender with race and Indigeneity, and articles with a non-Canadian or non–North American frame of reference. New approaches to questions of gender and power will be needed to challenge, enliven, and reinvigorate the field as it moves into the mid-twenty-first century.